Recent Advances on the Bovine Viral Diarrhea Virus Molecular Pathogenesis, Immune Response, and Vaccines Development - Al-Kubati, Anwar A. G.; Hussen, Jamal; Kandeel, Mahmoud; Al-Mubarak, Abdullah I. A.; Hemida, Maged Gomaa (Frontiers in Veterinary Science, 2021)
The bovine viral diarrhea virus (BVDV) consists of two species and various subspecies of closely related viruses of varying antigenicity, cytopathology, and virulence-induced pathogenesis. Despite the great ongoing efforts to control and prevent BVDV outbreaks and the emergence of new variants, outbreaks still reported throughout the world. In this review, we are focusing on the molecular biology of BVDV, its molecular pathogenesis, and the immune response of the host against the viral infection. Special attention was paid to discuss some immune evasion strategies adopted by the BVDV to hijack the host immune system to ensure the success of virus replication. Vaccination is one of the main strategies for prophylaxis and contributes to the control and eradication of many viral diseases including BVDV. We discussed the recent advances of various types of currently available classical and modern BVDV vaccines. However, with the emergence of new strains and variants of the virus, it is urgent to find some other novel targets for BVDV vaccines that may overcome the drawbacks of some of the currently used vaccines. Effective vaccination strategy mainly based on the preparation of vaccines from the homologous circulating strains. The BVDV-E2 protein plays important role in viral infection and pathogenesis. We mapped some important potential neutralizing epitopes among some BVDV genomes especially the E2 protein. These novel epitopes could be promising targets against the currently circulating strains of BVDV. More research is needed to further explore the actual roles of these epitopes as novel targets for the development of novel vaccines against BVDV. These potential vaccines may contribute to the global eradication campaign of the BVDV.